Activation of peroxymonosulfate by nitrogen-functionalized sludge carbon for efficient degradation of organic pollutants in water. (October 2017) - Sun, Hongwei; Peng, Xingxing; Zhang, Shuping; Liu, Shengwei; Xiong, Ya; Tian, Shuanghong; Fang, Jingyun
Graphical abstract: Highlights: Nitrogen-functionalized sludge carbon (NSC) was prepared. NSC was active for peroxymonosulfate (PMS) activation. Singlet oxygen was dominant reactive oxidative species in NSC/PMS system. Pyridine N, graphite N and pristine CO in the NSC framework are crucia Abstract: Nitrogen-functionalized sludge carbon (NSC) was prepared by urea-mediated pyrolysis of sewage sludge (SS) and was introduced, for the first time, as a potential metal-free catalyst to activate peroxymonosulfate (PMS) for oxidative removal of organic pollutants in water. The nitrogen functionalization of NSC catalysts significantly affected the chemical micro-environments as well as microstructures (morphology and porosity), improving the PMS activation activity towards removing various pollutants, e.g., acid orange 7, phenol and rhodamine B. On the basis of quenching studies and electron paramagnetic resonance, the formed dominant reactive oxidative species (ROS) in the NSC/PMS system was clarified to be nonradical singlet oxygen, in addition to the typical radical ROSs, sulfate and hydroxyl radicals. The incorporated pyridine N, graphite N and pristine CO in the NSC framework promoted the generation of ROS. This study provided new insights into environmentally friendly resourcing SS and exploiting novel cost-effective metal-free catalyst for PMS activation.